Entropy generation and heat convection analysis of second-grade viscoelastic nanofluid flow in a tilted lid-driven square enclosure: A finite difference approach - Anil Ahlawat; Mukesh Kumar Sharma; K. Loganathan (International Journal of Thermofluids)
Thermal management is crucial for effective heat regulation and minimal energy loss across fields like electronics cooling, chemical processing, and energy storage etc. Therefore, present work numerically analyzes the convection of heat and entropy production for a lid driven flow in a tilted square enclosure containing viscoelastic nanofluid exposed to a static magnetic field with a magnitude denoted as ‘B0’. A second-grade model is employed to characterize the viscoelastic behavior. Tc and Th are the constant temperatures at the upper and bottom walls, respectively whereas the vertical walls are considered insulated. Moreover, upper wall moves at a uniform velocity in positive x-axis direction. The stream function approach removes the pressure gradient term from the linear momentum equation, and the resulting partial differential equations are discretized via finite differences and then resulting algebraic equations are solved with SOR and SUR methods employing self-developed MATLAB codes. The computations were carried out with the values relevant parameters ranging from: 10  ≤ Re ≤ 50, 0 ≤  Ha ≤ 20, 0 % ≤ ϕnf ≤ 4 %, 10−1 ≤  Ec ≤ 10−3, 0 ≤ En ≤ 10−2 and inclination angle (ξ)= -300, 00, 300, 450. The contour profiles of streamlines, isotherms, local entropy generation (SGEN); local Bejan number (Be) are plotted to demonstrating their effects. It is noted that Nuavg and Ns both increase significantly as the ϕnf increases. However, rise in ‘Ha’, reduces Nuavg and Ns by 47.19 % and 43.42 % for Ri = 0.1, and by 4.17 % and 3.46 % for Ri = 5, respectively. The elasticity effect opposes flow and reduces Nuavg and Ns. At Ri = 0.1, increasing ‘En’ from 0 to 0.1 reduces Nuavg and Ns by 2.22 % and 2.56 %, while at Ri = 5, Nuavg and Ns decreases by 0.76 % and 0.28 %. Moreover, with Eckert number (Ec) average Nusselt number diminishes, accompanied by an increase in both Ns and Beavg. Heat convection and entropy production are enhanced with forward inclination of the square enclosure and is slightly diminished with backward inclination.